Creating online participatory research spaces: insights from creative, digitally mediated research with children during the COVID-19 pandemic. (1st February 2022) - Lomax, Helen; Smith, Kate; McEvoy, Jo; Brickwood, Eleanor; Jensen, Kathrine; Walsh, Belinda
Abstract : Our article draws on research undertaken with children during the 2020‐21 COVID-19 pandemic in order to consider the potential of digitally mediated participatory research for child-centred research practice. Our specific focus is on how children's inclusion can be centred in the absence of opportunities to meet in person. We reflect on how we sought to support children's engagement through offline and online creative activities and explore how these digitally mediated spaces can facilitate children's inclusion, creative engagement and dialogue. We offer examples from our arts-based, digitally mediated research to consider how researchers might work remotely, yet inclusively, in contexts where children have been marginalised and their voices silenced. Our research suggests that scaffolding creative activities through bespoke digital animation and asynchronous chat can facilitate children to participate in ways of their choosing. However, to address equity of inclusion researchers must attend to the contingencies of children's digital, material and social exclusion.